Therapeutic Potential of Plant-Derived Phytochemicals in Targeting Receptor Pathways Related to Non-Enzymatic Glycation: A Meta-Analysis - Mohammad Nadeem Khan (International Journal of Cell Biology and Cellular Functions, 2025)
Background: Non-enzymatic glycation, where reducing sugars react with proteins, lipids, and nucleic acids, contributes to various pathological conditions, such as diabetic complications and cardiovascular diseases. This process is facilitated by the receptor for advanced glycation end-products (RAGE), which is pivotal in driving inflammation and causing tissue damage. Objective: This meta-analysis evaluates the effects of plant-derived phytochemicals on RAGE expression and associated signaling pathways, assessing their therapeutic potential in glycation-related diseases. Methods: A systematic search identified 26 studies, including in vitro (n = 16) and animal models (n = 10). Statistical analysis was performed using standardized mean difference (SMD) to assess the impact of different phytochemicals on RAGE expression, with subgroup analyses by phytochemical type and experimental model. Findings: Results showed that flavonoids (e.g., quercetin and apigenin) had the most significant effects in reducing RAGE expression (SMD = –1.20), followed by polyphenols like resveratrol and curcumin (SMD = –0.70 to –0.85). Animal models exhibited greater efficacy in reducing RAGE expression compared to in vitro studies. These findings highlight the therapeutic potential of these compounds for managing diabetic nephropathy, cardiovascular diseases, and other glycation-related conditions. Conclusion: Plant-derived phytochemicals, particularly flavonoids and polyphenols, show promise as therapeutic agents targeting RAGE expression. Future research should focus on clinical trials, bioavailability, combination therapies, and personalized medicine to optimize their use in treating glycation-related diseases.
Keywords: Flavonoids; Non-enzymatic glycation; Phytochemicals; Polyphenols; curcumin; diabetic nephropathy; glycation-related diseases; quercetin; receptor for advanced glycation end-products (RAGE); resveratrol